Insights into the effects of pulsed antimicrobials on the chicken resistome and microbiota from fecal metagenomes - Ruo-nan ZHAO; Si-yuan CHEN; Cui-hong TONG; Jie HAO; Pei-si LI; Long-fei XIE; Dan-yu XIAO; Zhen-ling ZENG; Wen-guang XIONG (Journal of Integrative Agriculture, 2023)
Antimicrobial resistance has become a global problem that poses great threats to human health. Antimicrobials are widely used in broiler chicken production and consequently affect their gut microbiota and resistome. To better understand how continuous antimicrobial use in farm animals alters their microbial ecology, we used a metagenomic approach to investigate the effects of pulsed antimicrobial administration on the bacterial community, antibiotic resistance genes (ARGs) and ARG bacterial hosts in the feces of broiler chickens. Chickens received three 5-day courses of individual or combined antimicrobials, including amoxicillin, chlortetracycline and florfenicol. The florfenicol administration significantly increased the abundance of mcr-1 gene accompanied by floR gene, while amoxicillin significantly increased the abundance of genes encoding the AcrAB-tolC multidrug efflux pump (marA, soxS, sdiA, rob, evgS and phoP). These three antimicrobials all led to an increase in Proteobacteria. The increase in ARG host, Escherichia, was mainly attributed to the β-lactam, chloramphenicol and tetracycline resistance genes harbored by Escherichia under the pulsed antimicrobial treatments. These results indicated that pulsed antimicrobial administration with amoxicillin, chlortetracycline, florfenicol or their combinations significantly increased the abundance of Proteobacteria and enhanced the abundance of particular ARGs. The ARG types were occupied by the multidrug resistance genes and had significant correlations with the total ARGs in the antimicrobial-treated groups. The results of this study provide comprehensive insight into pulsed antimicrobial-mediated alteration of chicken fecal microbiota and resistome.